2021
DOI: 10.1007/s11739-021-02800-1
|View full text |Cite
|
Sign up to set email alerts
|

High-dose dexamethasone treatment for COVID-19 severe acute respiratory distress syndrome: a retrospective study

Abstract: Low-dose dexamethasone reduces mortality in patients with coronavirus disease 2019 (COVID-19)-related acute respiratory distress syndrome (ARDS). We retrospectively analyzed the efficacy of high-dose dexamethasone in patients with COVID-19-related ARDS and evaluated factors affecting the composite outcome (death or invasive mechanical ventilation). From March 4th to April 1st 2020, 98 patients with COVID-19 pneumonia were included. Those who after at least 7 days from symptom onset presented a worsening of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
(47 reference statements)
0
15
1
1
Order By: Relevance
“… 1 Moreover, the identification of early predictors for severe disease (i.e., low admission eGFR) 22 could help in the risk stratification to choose the best treatment strategies (i.e., high‐dose glucocorticoids treatment or other immunomodulating drugs). 21 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Moreover, the identification of early predictors for severe disease (i.e., low admission eGFR) 22 could help in the risk stratification to choose the best treatment strategies (i.e., high‐dose glucocorticoids treatment or other immunomodulating drugs). 21 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…First, the optimal timing for remdesivir administration to prevent disease progression and complication is still under evaluation 1 . Moreover, the identification of early predictors for severe disease (i.e., low admission eGFR) 22 could help in the risk stratification to choose the best treatment strategies (i.e., high‐dose glucocorticoids treatment or other immunomodulating drugs) 21,23 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, first-pass metabolism is thought to be impacted by the shunt effect, increasing a drug's bioavailability, yet the impact of shunting on the AUC0-24 and CL of DEX remained minimal. Simulations of DEX 20 mg IV and PO once a day were made since higher doses are being investigated to present clinical improvement and decrease in inflammatory biomarkers in patients hospitalized with COVID-19, but remain unproven (Vecchié et al, 2021). However, the AUC ratio between healthy and individuals with LD remained comparable to the lower dose (6 mg once a day), showing linear PK.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone, a synthetic corticosteroid, is a glucocorticoid used to treat asthma, allergic reactions, arthritis and other autoimmune diseases [ 83 ]. A retrospective observational study showed that a high dose of dexamethasone induced a significant improvement in clinical and laboratory parameters in hospitalized COVID-19 patients under the hyperinflammatory phase [ 84 ]. In another study, the effectiveness of low doses of dexamethasone was compared to the usually used high dosage [ 82 ].…”
Section: Corticosteroidsmentioning
confidence: 99%